(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
In this research, orange peel oil was extracted by cold soaking method with a new cheap solvent, light hydrogenated naphtha produced in Banias Refinery Company. The optimum conditions for the extraction process were determined and the best results were recorded at a soaking time of 60 hours and a solid/liquid ratio of 6:1. The possibility of mixing the extracted oil with petroleum diesel fuel with different weight ratios 6%, 4%, 2% was studied. An evaluation of the effect of blending was conducted and compared with the specifications of petroleum diesel before blending and with the Syrian Standard Specification No. /3447/ for the year /2009/. The results showed that the best mixing ratio was at 6% while maintaining the mixture achieving the required standard, where a decrease in sulfur percentage and an improvement in cetane number 53.11 were observed.